A ludicidade como estratégia no ensino de física no ensino fundamental - Fonseca, João Ferreira (2021)
Any action that requires a spontaneous concentration of energies with the objective of providing well-being can be defined as playful. As a pedagogical resource, it helps students to minimize difficulties, potentiate new concepts, adopting an active, harmonious, pleasurable learning process and lead their learning. A playful Scientific Literacy, allows students to understand their universe, have access to new cultures and knowledge in a more active way. Many challenges still need to be overcome in the classroom: boring classes, outdated methodologies, inadequate teacher training, the mathematization of physics. Presenting more pleasant, pleasant and efficient classes through tools that facilitate learning is one way. The playfulness and the pedagogical resource "Maleta Dinâmica" are presented in this work, where it is intended to improve interest, performance and learning in classes, especially physics. Vygotsky, Piaget, Wallon, Bruner and other contemporaries support the proposed proposal. This work discusses the transversality of playfulness in the teaching and learning process. To consolidate learning, brainstorming and mind maps were presented and built throughout the activities. The playful resources facilitated the understanding of Kinematics concepts. With elementary school students Isaac Newton was the protagonist. Comparing the answers allowed us to observe the evolution of learning about the concepts, as it involves playing in everyday life. With undergraduate students and teachers of basic education, the research sought to understand the role of the use of recreational resources in a pedagogical environment. Archimedes helps with concepts such as the center of gravity of plane figures, balance, scales and levers, volumetric bodies. Proposals for elaboration with low-cost materials, forming an integral part of the “suitcase”. The analysis of the answers to the questionnaires clarified that the playful resources and the educational product motivated the elementary school students and provided the teaching and learning process.